GAYA KEPEMIMPINAN, BEBAN KERJA, STRES KERJA, TEKNOLOGI INFORMASI, DAN KINERJA KARYAWAN - I Gusti Bagus Ari Pinatih; Anak Agung Ngurah Eddy Supriyadinata Gorda (Jurnal Ilmiah Manajemen & Bisnis, 2017)
Leadership style, workload, work stress, information technology, and performance of employees. The purpose of this study was to determine the effect of leadership style, workload, work stress, information technology, the performance of employees at PT. Bank Bukopin, Tbk. Denpasar Branch by analyzing the relationship between variables of leadership style, workload, work stress, information technology, and employee performance. Type of this research is quantitative with the questionnaire as a tool for data collection. For statistical analysis and hypothesis testing using Structural Equation Modeling (SEM). Respondents in this study were employees of PT. Bank Bukopin, Tbk. Branch Denpasar with 106 people in population. The results showed that only one variable that is not consistent with the hypothesis that no significant effect on the performance of the employee (workload). Style of leadership, information technology, and job stress produces positive and significant influence on employee performance. So, the company have to pay attention to the variables that affect the performance of employees in order to achieve the goals of the company. Keywords: leadership style, work load, work stress, information technology, and employee performance.